Analisis Penilaian Situs Geologi Sebagai Peluang Pengembangan Geowisata di Kabupaten Bantul, Daerah Istimewa Yogyakarta - Ali, Rinal Khaidar; Qadaryati, Nurakhmi; Kurniawan, Wahyu (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2021)
Bantul Regency, Special Region of Yogyakarta (DIY) has the natural resources with the potential of beauty and geological diversity which are the result of the past process that potentially become a geotourism area. This research is conducted to identify the potential of geosites, by finding and mapping geological sites scattered in this region. The research is conducted by using literature review methods, field observations, laboratory analysis, geological site assessment analysis. Geosite assesment analysis method is done by using assessment according to Kubalikova, 2013 which is used to provide an assessment of the feasibility of the geological sites location. The result of quantitative analysis of the assessment method that is conducted shows that there are only 8 (eight) geological sites that are possible to be developed into geotourism objects. Based on all the sites found, 2 (two) routes of geotrack tour were made, namely the west route and the east route. Keywords: Bantul; Geosite; Kubalíková; Geotourism